Rang's Children's Fractures. - Wenger, Dennis R. (Wolters Kluwer Health, 2005)
Dr. Mercer Rang's classic text on children's fractures has been revised and updated by two eminent orthopedic surgeons from Children's Hospital-San Diego. Continuing Dr. Rang's tradition, Drs. Wenger and Pring provide a uniquely practical, readable overview of children's fractures, emphasizing diagnosis, treatment, common pitfalls, and communication with parents and other healthcare professionals. This edition features over 400 new illustrations. New chapters cover casts and epidemiology and prevention of fractures. Elbow injuries are covered in greater detail in two chapters. New information.